Pembangunan Modul Triz Secara Pencantasan untuk Pembelajaran Berasaskan Masalah - Heong, Yee Mei; Sharberi, Siti Nur Maizura; Abu Bakar, Nurulhuda; Ching, Kok Boon; Mohamad, Mimi Mohaffyza (Online Journal for TVET Practitioners, 2020)
Inventive Problem Solving Theory (TRIZ) is a problem-solving method that can be used in Problem-Based Learning (PBL). Therefore, this study aimed to generate a learning module for integrating TRIZ integrally into PBL. The learning module is a technique that enables teaching and learning to be performed individually. With this, students can take each unit step by step. In addition, this study also identifies the suitability of the format, content and usability of the TRIZ integration module in its in-depth PBL. This study used a quantitative method involving five lecturers and 10 students at UTHM who were randomly selected as the study sample. The data were analyzed descriptively and presented in frequency and percentage using Microsot Excel 2013. Based on the findings of the study, the majority of lecturers and students agreed that the format and content of the TRIZ integration learning modules in a nutshell is appropriate and usable in PBL. In conclusion, it can be concluded that the module developed can be used as a source of reference for lecturers and students to solve inventive problems and PBL during the teaching and learning process.